22. ANALISIS PENYEBAB PRAKTIK KERJA PAKSA DI ARAB SAUDI: FENOMENA KERJA PAKSA TERHADAP TKI INFORMAL (2011-2014) - Rizka Puspitasari; Reni Windiani; Marten Hanura (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2016)
TKI is foreign exchange hero for Indonesia. TKI send remittances to Indonesia about tens oftrillions rupiah. However, the contribution of remittances is not balanced with the guaranteeof TKI human rights protection. Informal workers sector or domestic workers was the mostvulnerable sector to human rights violations, including forced labour, such as unpaid wages,the job does not match with the contract of employment, confinement, and physical andpsychological violence. One of the major destination countries of TKI placement is SaudiArabia, where about 40% of the total number of TKI torture and deaths occur there. SaudiArabia is a member state that has ratified the International Labour Organization (ILO)concerning forced labor, which are the Forced Labour Convention (No. 29) and the Abolitionof Forced Labour Convention (No. 105). However, the practice of forced labor is still foundunresolved, including against informal sector workers. This study aims to find out why forcedlabour Saudi Arabia could have. In answering these objectives, this study uses constructivismparadigm and compliance theory. The method used in this research is qualitative method withdescriptive-analytical type through interviews and literature technics. Results from this studyis that there are three factors that cause forced labour in Saudi Arabia, they are Saudi Arabiahas not yet understand the provisions of the convention because of the applied domesticnorms there, then Saudi Arabia has limited capacity to conduct labour inspection, and theabolition of forced labor is not a priority interest of Saudi Arabia.